2007
DOI: 10.1016/j.febslet.2007.07.073
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish erythropoietin: Functional identification and biochemical characterization

Abstract: In the present study, the zebrafish epo cDNA was cloned. The encoded protein displays 90%, 55% and 32% identity to the Epo from carp, fugu and human, respectively. Through RT-PCR, the expression of zepo mRNA was mainly in the heart and liver. In the COS-1 cell transfection experiments, the recombinant zEpo-HA protein was efficiently secreted into the culture medium as a glycoprotein and the carbohydrate moiety can be cleaved by the treatment of peptide-N-glycosidase F (PNGase F). Using the morpholino approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 24 publications
5
38
0
Order By: Relevance
“…We further have discovered that a major source of Epo for primitive erythropoiesis might be a subpopulation of neural and neural crest cells, which we refer to as NEP cells. Consistent with our observation, the principal Epo-producing tissue in zebrafish larvae is neural tissue, and Epo production moves to the heart and liver during adulthood 40,41 . We also observed that a subpopulation of NEP cells migrate along the blood vessels in the intersomitic space.…”
Section: Discussionsupporting
confidence: 77%
“…We further have discovered that a major source of Epo for primitive erythropoiesis might be a subpopulation of neural and neural crest cells, which we refer to as NEP cells. Consistent with our observation, the principal Epo-producing tissue in zebrafish larvae is neural tissue, and Epo production moves to the heart and liver during adulthood 40,41 . We also observed that a subpopulation of NEP cells migrate along the blood vessels in the intersomitic space.…”
Section: Discussionsupporting
confidence: 77%
“…The first Epo gene fish cloned was that of the pufferfish (Fugu; Takifugu rubripes). In Fugu, Epo is induced by hypoxia and is mainly expressed in the heart [80][81][82]. However, in other teleost fishes, such as rainbow trout, carp, and eel, Epo was expressed in the kidney, the kidney is the major organ for erythropoiesis in fishes [83].…”
Section: Hypoxia Adaptation Mechanisms In Fishesmentioning
confidence: 99%
“…2, pathway 7). In zebrafish, heart and liver were shown to be the major Epo-producing organs (154). Although myocardial Epo expression may be induced by hypoxic exposure (155) the origin of endogenous Epo secreting cells in the mammalian heart is unknown.…”
Section: Epor In the Heartmentioning
confidence: 99%